Improvement of Methodological Tools for Business Analysis of the Effective Company’s Performance - N. S . Plaskova (Управленческие науки, 2022)
The subject of the paper is the improvement of methodological approaches to the formation of an objective assessment of the system of financial indicators that comprehensively reflect the achieved and projected level of development of economic entities. In these conditions, the issues of substantiating the perimeter and content of the information and analytical support system for the functions of operational and strategic business management are being updated. The purpose of the study is to develop methods of analysis and algorithms for calculating the most important characteristics of assessing the performance of economic entities for internal management and external stakeholders based on a complementary approach to the use of classical methods of forming a piece of information and analytical base by clarifying the values of the indicators used in financial and management reporting and supplementing the list of analytical indicators. To achieve the goal, the author has identified several tasks related to the critical analysis of the existing methodological apparatus for evaluating the performance of commercial organizations. Also, the author updated the content, and clarified the algorithms for calculating indicators to form reliable information and analytical base necessary for making managerial decisions by various subjects of business relations. The author analyzed the supplementing the system of analytical indicators for assessing and forecasting business performance in accordance with the doctrine of sustainable development; expansion of the model range of factor analysis to get a holistic view of the impact of external and internal drivers on the level of financial stability and profitability of business entities. To substantiate the scientific hypothesis, form methodological provisions within the scope of the research, generalize the empirical base and develop practical proposals, the research clarified and supplemented the algorithms for calculating several performance indicators traditionally used in analytical practice, as well as initial indicators of financial and management reporting, have been involved. The practical application of the proposed adjusted procedures for calculating indicators contributes to getting a reliable and aimed assessment of the quality of the management system of organizations in the real sector of the economy. Also, it promotes a reliable measurement of the influence of factors of the external and internal business environment on its effectiveness, the development of an optimal resource potential management policy in order to increase competitiveness, strengthen financial stability and increase investment attractiveness.